2022
DOI: 10.1007/s41365-022-01091-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in two-proton radioactivity

Abstract: During the last few decades, rare isotope beam facilities have provided unique data for studying the properties of nuclides located far from the beta-stability line. Such nuclei are often accompanied by exotic structures and radioactive modes, which represent the forefront of nuclear research. Among them, two-proton (2p) radioactivity is a rare decay mode found in a few highly proton-rich isotopes. The 2p decay lifetimes and properties of emitted protons hold invaluable information regarding the nuclear struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 215 publications
0
3
0
Order By: Relevance
“…This result can be interpreted as the fact that current theoretical methods almost all regard the 2p radioactivity as the only diproton emission case [40][41][42][43][44][45]. For the not true 2p radioactivity whose Q 2p > 0 and Q p > 0 and the true 2p radioactivity whose two protons are emitted with large opening angles in the direction of emission, the cases of cascade emission and three-body emission should also be further considered [39,70]. Nevertheless, it remains appropriate for the systematic investigations of the 2p radioactivity utilizing the diproton emission model at present, particularly for the true 2p radioactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be interpreted as the fact that current theoretical methods almost all regard the 2p radioactivity as the only diproton emission case [40][41][42][43][44][45]. For the not true 2p radioactivity whose Q 2p > 0 and Q p > 0 and the true 2p radioactivity whose two protons are emitted with large opening angles in the direction of emission, the cases of cascade emission and three-body emission should also be further considered [39,70]. Nevertheless, it remains appropriate for the systematic investigations of the 2p radioactivity utilizing the diproton emission model at present, particularly for the true 2p radioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cascade emission can be viewed as a double sequential emission. Owing to the involvement of nucleon wave function configurations and nucleon-nucleon interaction in the two correlated protons, the first two mechanisms attract the interest of researchers [39]. For the estimation of the 2p decay rate, one of the viable theoretical methods of calculating the 2p radioactive half-lives is the semiclassical Wentzel-Kramers-Brillouin (WKB) approximation.…”
Section: Introductionmentioning
confidence: 99%
“…A review of recent progress can be found in Ref. [3]. The 2p radioactivity occurs in even-Z nuclei where one proton emission is energetically forbidden while 2p emission is allowed.…”
Section: Introductionmentioning
confidence: 99%